PROBLEMATIKA HUKUM DALAM PENERAPAN SANKSI PIDANA KEBIRI KIMIA BAGI PELAKU TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI INDONESIA - Krisananda, Aldi; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Punishment against the perpetrators of sexual violence against children as stipulated in law number 17 of 2016 concerning the protection of Children, with the threat of punishment to a maximum of 20 years in prison until chemical castration punishment for perpetrators. Sexual violence against children in Indonesia continues to increase, with the passing of law number 17 of 2016 concerning child protection, which includes the punishment of medical ethics in Indonesia. In terms of human rights, chemical castration punishment is torture and humiliates human dignity, whereas in the medical code of ethich, chemical castration is a punishment that violates the doctor’s oath states that every doctor must prioritize the patient’s healthThis type of research is used by using normative juridical research, namely legal research conducted by examining the standard rules that have been recorded. The focus is to examine what are the problems in the application of chemical castration criminal sanctions in Indonesia.From the results of the study showed that castration punishment does not conflict with human rights because castration punishment is a prevention so that the perpetrator does not become a sexual predator. Castration punishment included in the combined theory of this theory considers the imposition of punishment in retaliation as well as fixing the offender so as not to commit a crime of sexual violence against children. And the executor of perpetrators of sexual violence against children is carried out by the Indonesian National Police through the Police Doctor (Dokpol) and the responsibility is no longer on IDI but on the State.Keywords: Human Right, Castration Penalty, Medical.